Analysis of the prevalence of dental and occlusal anomalies in children and adolescents in Poland and elsewhere – review of the publications from the last 10 years - Dorota Cudziło; Agnieszka Sikorska; Maja Matthews-Kozanecka; Teresa Matthews-Brzozowska (Journal of Medical Science, 2018)
Introduction. Dental and occlusal anomalies constitute a very common disorder of the mastication organ. The objective of this work was to analyse papers published over the last decade on the prevalence of the mastication irregularities in Poland and elsewhere. Material and Methods. The work analyses 22 publications, i.e. 6 papers on disorders in children and adolescents in Poland and 16 papers discussing such abnormalities elsewhere. Results. Prevalence of malocclusion in the population of children and adolescents in Poland fluctuates between 52.5% and 88%, depending on the region. As regards scientific works published abroad, malocclusion oscillates between 33% and 95.6%, depending on the country. Conclusions. Occlusal defects are diagnosed in children and adolescents both in Poland and elsewhere and the prevalence of the mastication anomalies depends neither on race nor on ethnic origin.